2010
DOI: 10.1002/pon.1764
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning‐Making intervention (MMi) appears to increase meaning in life in advanced ovarian cancer: a randomized controlled pilot study

Abstract: The MMi seems a promising intervention for advanced cancer patients, and a full randomized controlled trial is warranted to further investigate its efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
157
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(163 citation statements)
references
References 14 publications
(25 reference statements)
4
157
0
2
Order By: Relevance
“…[37][38][39][40][41] Early interventions designed to promote positive psychological resources have shown promise in adults with cancer, [42][43][44][45][46] healthy AYAs, 47,48 and AYAs undergoing hematopoietic stem cell transplant for malignancy. 49 We have previously shown that self-perceptions of personal resources mediate these associations.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40][41] Early interventions designed to promote positive psychological resources have shown promise in adults with cancer, [42][43][44][45][46] healthy AYAs, 47,48 and AYAs undergoing hematopoietic stem cell transplant for malignancy. 49 We have previously shown that self-perceptions of personal resources mediate these associations.…”
Section: Discussionmentioning
confidence: 99%
“…Directly integrating spirituality into psychotherapy may be similarly effective for improving quality of life for those with cancer (Garlick, Wall, Corwin, & Koopman, 2011). An existential intervention that focuses specifically on meaning-making has also shown promise for individuals with breast, colorectal, and ovarian cancer (Henry et al, 2010; Lee, Cohen, Edgar, Laizner, & Gagnon, 2006) and may be particularly well-suited to the HSCT setting given the brief, flexible approach.…”
Section: Discussionmentioning
confidence: 99%
“…In MMI, the patient engages in up to 4 sessions of individual therapy to ''focus systematically on situational, global, and existential meaning'' 39(p1341) while incorporating past significant life events, priorities, and goals into the patient's understanding of his or her diagnosis. 39 Using the HADS scale, the study did not find that the MMI had a significant effect on mood.…”
Section: Meaning-making Interventionmentioning
confidence: 97%